Nanocellulose-stabilized Pickering emulsions: Fabrication, stabilization, and food applications - Ji, Chuye; Wang, Yixiang (Advances in colloid and interface science, 2023)
Pickering emulsions have been widely studied due to their good stability and potential applications. Nanocellulose including cellulose nanocrystals (CNCs), cellulose nanofibrils (CNFs), and bacterial cellulose nanofibrils (BCNFs) has emerged as sustainable stabilizers/emulsifiers in food-related Pickering emulsions due to their favorable properties such as renewability, low toxicity, amphiphilicity, biocompatibility, and high aspect ratio. Nanocellulose can be widely obtained from different sources and extraction methods and can effectively stabilize Pickering emulsions via the irreversible adsorption onto oil-water interface. The synergistic effects of nanocellulose and other substances can further enhance the interfacial networks. The nanocellulose-based Pickering emulsions have potential food-related applications in delivery systems, food packaging materials, and fat substitutes. Nanocellulose-based Pickering emulsions as 3D printing inks exhibit good injectable and gelling properties and are promising to print spatial architectures. In the future, the utilization of biomass waste and the development of “green” and facile extraction methods for nanocellulose production deserve more attention. The stability of nanocellulose-based Pickering emulsions in multi-component food systems and at various conditions is an utmost challenge. Moreover, the case-by-case studies on the potential safety issues of nanocellulose-based Pickering emulsions need to be carried out with the standardized assessment procedures. In this review, we highlight key fundamental work and recent reports on nanocellulose-based Pickering emulsion systems. The sources and extraction of nanocellulose and the fabrication of nanocellulose-based Pickering emulsions are briefly summarized. Furthermore, the synergistic stability and food-related applications of nanocellulose-stabilized Pickering emulsions are spotlighted. [Display omitted] •It is favorable to obtain nanocellulose from waste by using recyclable chemicals.•Amphiphilicity and morphology of nanocellulose determine the emulsifying capacity.•Synergistic stabilization by nanocellulose complexes is an effective strategy.•Food applications focus on encapsulation, food packaging, and fat substitute.•New technology such as 3D printing enables new opportunity while challenges exist.